Activation and expression of proteins during synchronous germination of aerial spores of Streptomyces granaticolor - Bobek, Jan; Halada, Petr; Angelis, Jakub; Vohradský, Jiri; Mikulík, Karel (Proteomics, 2004)
Synchronously germinating aerial spores of Streptomyces granaticolor were used to study protein activation and expression during the transition from dormant to metabolically active vegetative forms. The first phase of protein activation is associated with the solubility of proteins. Three major chaperones, DnaK, Trigger factor, and GroEL, were identified in spores. Enhancement in rate of protein synthesis during germination was accompanied by the association of TF and DnaK with ribosomes. During germination, the chaperones TF, GroEL, and DnaK undergo reversible phosphorylation. GroEL was phosphorylated on both Ser and Thr, whereas phosphorylation of DnaK and TF was detected on Thr only. A proteomic approach was used to gain more information on protein expression during germination on two types of media differing in the ability of cells to produce antibiotic granaticin. To obtain an overview of the metabolic activity of germinating spores, glycolytic enzymes, enzymes of citric acid cycle, metabolism of amino acids and nucleic acids, and components of the protein synthesis system were identified and analyzed using the proteomic database. The results were deposited on the SWICZ proteomic server and are accessible on http://proteom.biomed.cas.cz.
Keywords: Ribosomes; proteiny tepelného šoku HSP70; isoelektrická fokusace; AMP cyklický; databáze proteinů; 2D gelová elektroforéza; Kinetics; proteosyntéza; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; naftochinony; teplota; threonin; vysokoúčinná kapalinová chromatografie; Time Factors; časové faktory; chaperon hsp60; DNA; Methionine; Spores, Bacterial; proteomika; Naphthoquinones; RNA; proteiny z Escherichia coli; Proteins; Temperature; hmotnostní spektrometrie s elektrosprejovou ionizací; Proteomics; Macromolecular Substances; Chromatography, High Pressure Liquid; proteiny; Cyclic AMP; HSP70 Heat-Shock Proteins; Chaperonin 60; fosforylace; Databases, Protein; Streptomyces; methionin; Electrophoresis, Gel, Two-Dimensional; Protein Biosynthesis; Isoelectric Focusing; makromolekulární látky; ribozomy; Threonine; peptidylprolylisomerasa; spektrometrie hmotnostní - ionizace laserem za účasti matrice; glykolýza; Glycolysis; spory bakteriální; Peptidylprolyl Isomerase; kinetika; Spectrometry, Mass, Electrospray Ionization; Escherichia coli Proteins; Phosphorylation